Effects of Pilates and Classical Kinesiotherapy on chronic low back pain: a case study - Ivanna Avila Ribeiro; Tiago Damé de Oliveira; Cleci Redin Blois
Abstract Introduction : Chronic low back pain (LBP) is characterized by daily lower back pain lasting more than three consecutive months. It may lead to functional disability and can be treated by several physical therapy techniques, including therapeutic exercise. The aim of this study was to investigate the effects of pilates and classical kinesiotherapy on the treatment of pain and functional disability in patients with chronic low back pain. Materials and methods : The study sample consisted of five patients with a diagnosis of chronic low back pain and a mean age of 32.4 ± 15.6 years. A Visual Analogue Scale (VAS) was used for pain assessment, and the Oswestry Disability Index was used to assess functional disability at the beginning and at the end of the intervention. Patients were divided into two groups and received 20 individual sessions of therapeutic exercise at a frequency of two sessions per week. Group A was treated with classical kinesiotherapy and group B was treated with pilates exercises. Statistical analysis was performed using Wilcoxon's test. The significance level was set at 5%. Results : There was a significant reduction in pain (p = 043) and functional disability (p = 042) in both groups. We found no significant differences between the effects of pilates and classical kinesiotherapy on pain and functional disability. Conclusions : We conclude that, in the population studied here, both pilates and classical kinesiotherapy were effective in treating chronic low back pain symptoms, with no significant difference between them.